Can increased prenatal exposure to thyroid hormones alter physiology and behaviour in the long-term? Insights from an experimental study in Japanese quails - Aho, Kalle; Stier, Antoine; Sarraude, Tom; Hsu, Bin-Yan; Ruuskanen, Suvi (PeerJ, 2026)
Maternal thyroid hormones (triiodothyronine T3 and thyroxine T4) are important regulators of embryonic development and gene expression. In chickens, prenatal thyroid hormone treatment has been shown to influence embryonic gene expression and postnatal treatment to influence imprinting and learning. However, the potential long-term effects of maternal thyroid hormones on physiology and behaviour are unclear. This study aims to investigate the long-term effects of maternal thyroid hormones on behaviour, plasma thyroid hormone levels and brain gene expression using the Japanese quail (Coturnix japonica) as a model. Egg hormone levels were elevated by injecting unincubated eggs with either saline (control), T3, T4 or a mixture of T3 and T4. Social motivation, boldness and fearfulness to predators were tested shortly after hatching and as adults. Plasma thyroid hormone levels and pallial expression of thyroid hormone receptor A, type 2 deiodinase, and nuclear receptor coactivator 1 were measured in adulthood. We found no evidence that elevated thyroid hormone levels in eggs affected behaviour, plasma hormone levels, or gene expression in Japanese quails. This is the first study examining the potential long-term effects of elevated maternal thyroid hormones within the natural range. Although we found no evidence of long-term effects, other traits may still be affected and remain to be studied.